Platelet Count and Mean Platelet Volume in First Trimester are the Predictors of Preterm Premature Rupture of Membranes (Journal of Rangpur Medical College, 2025)
Background: Preterm Premature Rupture of Membranes (PPROM) complicates up to 3% of pregnancies and is associated with 30-40% of preterm birth. Objective: To find out the values of Platelet Count (PC) and Mean Platelet Volume (MPV) during first trimester of pregnancy to predict preterm premature rupture of membranes (PPROM). Methods: This prospective cohort study was conducted on 75 study subjects in Department of Fetomaternal Medicine and Obstetrics and Gynaecology, BSMMU, after taking approval from Institutional Review Board (IRB). Non-random purposive sampling technique was followed. After taking consent and matching eligibility criteria, data were collected from subjects on variables of interest using the structured designed by interview, observation, clinical examination and haematological investigation PC and MPV of subjects at 11 – 13 weeks of gestation. Levels of PC and MPV were documented, and participants were followed until delivery and also advised to report immediately if they experienced symptoms of PPROM. During the follow up, two participants were dropped out. Data were recorded on separate sheets for each participant and analyzed using SPSS 22.0 software. Result: In comparison with non PPROM, PPROM had significantly increasedthe level of PC and significantly decreased level of MPV in the first trimester of PPROM. The cut off value of the MPV _8 fL and PC _294,000/cu.mm. Sensitivity and Specificity of MPV 77.8% and 93.8% and Sensitivity and Specificity of PC were 66.7 % and 70.3%. Subjects with Platelet Count (PC) _294000/cu.mm had 3.84 times higher risk to develop PPROM and MPV _8fL had 19.73 times the higher risk to have PPROM. The overall accuracy of MPV for detecting PPROM was found to be superior to the Platelet Count (PC). Conclusion: Low MPV and high PC at first trimester of pregnancy are predictors of PPROM.J Rang Med Col. March 2025; Vol.10, No.1: 28-33